2022
DOI: 10.3389/fimmu.2022.855795
|View full text |Cite
|
Sign up to set email alerts
|

Eryptosis as a New Insight in Malaria Pathogenesis

Abstract: Eryptosis is a programmed cell death-like process that occurs in red blood cells. Although the red blood cells are anucleated, there are similarities between eryptosis and apoptosis, such as increased calcium efflux, calpain activation, phosphatidylserine exposure, cell blebbing and cell shrinkage. Eryptosis occurs physiologically in red blood cells, as a consequence of the natural senescence process of these cells, but it can also be stimulated in pathological situations such as metabolic syndromes, uremic sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…RBC-targeting inhibitors may elicit toxicity through off-target activity or activity secondary to engagement of the primary, annotated target. Some drugs stimulate reactive oxygen species ( Deavall et al., 2012 ), and for erythrocytes oxidative damage can induce eryptosis and rapid clearance from the bloodstream ( Dreischer et al., 2022 ; Scovino et al., 2022 ). As a proxy for erythrotoxic action of small molecules, we measured phosphatidylserine (PS) exposure ( Dreischer et al., 2022 ; Scovino et al., 2022 ) and hemolysis following treatment of RBCs by flow-cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RBC-targeting inhibitors may elicit toxicity through off-target activity or activity secondary to engagement of the primary, annotated target. Some drugs stimulate reactive oxygen species ( Deavall et al., 2012 ), and for erythrocytes oxidative damage can induce eryptosis and rapid clearance from the bloodstream ( Dreischer et al., 2022 ; Scovino et al., 2022 ). As a proxy for erythrotoxic action of small molecules, we measured phosphatidylserine (PS) exposure ( Dreischer et al., 2022 ; Scovino et al., 2022 ) and hemolysis following treatment of RBCs by flow-cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Some drugs stimulate reactive oxygen species ( Deavall et al., 2012 ), and for erythrocytes oxidative damage can induce eryptosis and rapid clearance from the bloodstream ( Dreischer et al., 2022 ; Scovino et al., 2022 ). As a proxy for erythrotoxic action of small molecules, we measured phosphatidylserine (PS) exposure ( Dreischer et al., 2022 ; Scovino et al., 2022 ) and hemolysis following treatment of RBCs by flow-cytometry. Among the durably acting antimalarial inhibitors ( Figure 2 ), Yoda1 and IPA-3 elicited the most profound effect (~30-60% of RBCs with PS exposure at 24h), with Yoda1 also exhibiting a rapid onset of hemolysis comparable to control compound A23187 ( Figure 3 ; Supplementary Table 1 ) – both compounds have previously been reported to stimulate eryptosis ( Zelenak et al., 2011 ; Wadud et al., 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Results show that transforming an image of qPCR-to qPCR+ necessitates generation of more anemia cells. Indeed the translation from a blood cell of a healthy patient to the blood cell of an infected patient seems to wipe a part of the hemoglobin content which, while not specific to the malaria infection, tends to denote an infectious context (White 2018; Scovino, Totino, and Morrot 2022). Furthermore, we also found that some cells were transformed into crenated cells which were previously reported to be related to certain liver diseases (Privitera and Meli 2016).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, not only infected RBCs undergo this cell death. This phenomenon is also common for non-infected cells, which may worsen anemia in patients with malaria [18]. Despite the numerous knowledge gaps in understanding the physiology and pathophysiology of eryptosis, its pharmacological modulation with therapeutic intentions has been widely investigated, in particular, in case of malaria [19].…”
Section: Introductionmentioning
confidence: 99%